Pembelajaran Saintifik Berbasis Pengembangan Karakter - Muhammad Nur Hakim; Fitriyani Dwi Rahayu (Nazhruna: Jurnal Pendidikan Islam, 2019)
Education in Indonesia is currently supposed to be able to create a quality human being and character. Many people who have a broad knowledge but do not have good morals, giving rise to various problems related to morals. The formation of character students can begin from family, school and community. In developed countries the formation of character can start by applying an appropriate curriculum. By using scientific learning, curriculum 2013 is expected to form the character of students in accordance with the 18 characters that are desired by the Government, that is: religious, honest, tolerance, discipline, hard work, creative, independent, democratic, curiosity, passion, love of the fatherland, to appreciate the achievements, communicative, peace-loving, an avid reader, care for the environment, social care, and responsibility. The character values that are integrated in the scientific learning through observing activities, ask yourself, try, analyze, and communication. With a scientific approach in the curriculum of 2013, educators are able to make learning more fun, more active, more challenging, and more to give space to the students to develop their creativity and potential, and make students become more self help in addressing a problem. Keywords: 2013 Curriculum, Scientific Learning, Character Education